Journal of the Marine Biological Association of the United Kingdom - Journal of the Marine Biological Association of the United Kingdom (Cambridge University Press, 2026)
Journal of the Marine Biological Association UK (JMBA) is an international journal, publishing original research and reviews on all aspects of marine biology, to support the aims of the MBA. The topics of present interest for JMBA are: - Marine ecology, behaviour and fisheries; - Biodiversity and population studies of marine ecosystems, especially potential impacts of global warming, ocean acidification and climate change on ecosystem resilience; - Physiology, biochemistry, genetics and molecular biology of marine organisms, including microbiology, particularly related to the integrative ecophysiology of marine organisms - Taxonomic syntheses, including molecular phylogenies; - Morphology, life history and developmental biology of marine organisms, especially model systems; - Chemical and physical oceanography, as directly relevant to marine biology; - Marine environmental health, and in particular its relationship to human health and well-being. In addition to papers describing original research, the journal will also publish short reviews and original viewpoints on topics of current marine biological interest.
FI 0.43
Q3
Keywords: Life Sciences; Marine Biology; Biología marina; Acuerdos transformativos; Transformative agreements; Ecología marina; Ecosistemas marinos; Cambio climático; Oceanografía química y física; Salud ambiental marina